2022
DOI: 10.1021/acssuschemeng.2c01550
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis and Parameter Optimization for the Fractionative Catalytic Conversion of Lignocellulosic Biomass in the Polyoxometalate–Ionosolv Concept

Abstract: The recently developed polyoxometalate (POM)− ionosolv concept offers an interesting strategy to generate two valuable product streams from lignocellulosic biomass, a solid cellulose-rich pulp and short-chain carboxylic acids like formic acid and acetic acid in a simple and cost-efficient manner. This study aimed to find optimum parameters for the two steps of the transformation by performing a sensitivity analysis on the initial ionosolv fractionation step as well as kinetic investigations of the following PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Higher water content in the reaction solution also leads to higher FA yields. In addition, also a higher FA selectivity was observed [123] . Furthermore, the authors showed that the HPA‐5 catalyzed system is also applicable for the conversion of softwood (pine) and grass with cellulose recoveries of 33 % for pine and 38 % for grass (60 % and 71 % cellulose content in the pulp).…”
Section: Catalytic Applications Using Bio‐based Feedstockmentioning
confidence: 94%
See 4 more Smart Citations
“…Higher water content in the reaction solution also leads to higher FA yields. In addition, also a higher FA selectivity was observed [123] . Furthermore, the authors showed that the HPA‐5 catalyzed system is also applicable for the conversion of softwood (pine) and grass with cellulose recoveries of 33 % for pine and 38 % for grass (60 % and 71 % cellulose content in the pulp).…”
Section: Catalytic Applications Using Bio‐based Feedstockmentioning
confidence: 94%
“…The cellulose remains in the solid‐state, whereas the lignin is dissolved and can later be precipitated by adding precipitating agents (Figure 15). [123] …”
Section: Catalytic Applications Using Bio‐based Feedstockmentioning
confidence: 99%
See 3 more Smart Citations